2013
DOI: 10.1007/s12272-013-0230-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB transcriptional activation in HepG2 cells by diterpenoids from the soft coral Sinularia maxima

Abstract: Anti-inflammatory transcriptional effects of nineteen compounds (1–19) from the soft coral Sinularia maxima were evaluated using NF-κB luciferase and reverse transcriptase polymerase chain reaction. Compounds 1, 2, 4, 8, 15, 17, and 18 significantly inhibited TNFα-induced NF-κB transcriptional activity in HepG2 cells in a dose-dependent manner, with IC50 values ranging from 15.81 ± 2.29 to 29.10 ± 1.54 μM. Furthermore, the transcriptional inhibitory function of these compounds was confirmed by a decrease in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…779 A modular approach to a number of cladiellin MNPs using a gold-catalysed tandem reaction of 1,7-diynes has been reported. 780 Hippuristanol (Isis hippuris) 781 analogues have been evaluated as inhibitors of eukaryotic translation initiation, 782 cembranoid and ergosterol MNPs from Vietnamese cnidarians were found to exhibit selective in vitro activity against T. brucei, 783 a number of diterpenes (Sinularia maxima) were found to be modest to poor inhibitors of NF-kB transcriptional activation, 784 structurally simpler analogues of fuscol/eunicol exhibit comparable or better anti-inammatory activity in the mouse ear edema assay, 785 semi-synthetic oxygenated dolabellane diterpenes exhibit in vitro anti-HIV activity, 786 further semisynthetic examples of hydoxysterols were found to induce pregnane X receptor transactivation, 787 exibilide 788 exhibits in vivo anti-neuroinammatory activity in rats, 789 11-epi-sinulariolide acetate inhibits carcinoma cell migration and invasion by suppressing a number of phosphorylationdependent pathways, 790 13-acetoxysarcocrassolide induces apoptosis in carcinoma cells by activation of p38/JNK and suppression of PI3K/AKT pathways, 791 and cembranoids from Sarcophyton glaucum exhibit cytotoxicity towards a murine melanoma cell line. 792,793 9 Bryozoans There were only three reports (containing 19 compounds) of new metabolites isolated from bryozoans in 2014, which is a large increase on 2013 when only one new metabolite was reported from this understudied phylum.…”
Section: Cnidariansmentioning
confidence: 99%
“…779 A modular approach to a number of cladiellin MNPs using a gold-catalysed tandem reaction of 1,7-diynes has been reported. 780 Hippuristanol (Isis hippuris) 781 analogues have been evaluated as inhibitors of eukaryotic translation initiation, 782 cembranoid and ergosterol MNPs from Vietnamese cnidarians were found to exhibit selective in vitro activity against T. brucei, 783 a number of diterpenes (Sinularia maxima) were found to be modest to poor inhibitors of NF-kB transcriptional activation, 784 structurally simpler analogues of fuscol/eunicol exhibit comparable or better anti-inammatory activity in the mouse ear edema assay, 785 semi-synthetic oxygenated dolabellane diterpenes exhibit in vitro anti-HIV activity, 786 further semisynthetic examples of hydoxysterols were found to induce pregnane X receptor transactivation, 787 exibilide 788 exhibits in vivo anti-neuroinammatory activity in rats, 789 11-epi-sinulariolide acetate inhibits carcinoma cell migration and invasion by suppressing a number of phosphorylationdependent pathways, 790 13-acetoxysarcocrassolide induces apoptosis in carcinoma cells by activation of p38/JNK and suppression of PI3K/AKT pathways, 791 and cembranoids from Sarcophyton glaucum exhibit cytotoxicity towards a murine melanoma cell line. 792,793 9 Bryozoans There were only three reports (containing 19 compounds) of new metabolites isolated from bryozoans in 2014, which is a large increase on 2013 when only one new metabolite was reported from this understudied phylum.…”
Section: Cnidariansmentioning
confidence: 99%
“…Inflammation plays a crucial role in many physio/pathological states, and different cell populations are involved in all phases of inflammatory process, including neutrophils, dendritic cells, monocytes/macrophages, and lymphocytes. Previous findings suggested that marine diterpenoids elicit among numerous activities, anti-inflammatory effects on murine macrophages [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 47 , 53 ]. In this study, starting from a previous drug discovery study aimed to fractionate marine samples, we successfully demonstrated that the sponge metabolite DHG possesses promising anti-inflammatory properties in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Cembranoids such as gibberosenes, grandilobatin, sarcocrassocolides, querciformolides, crassarines, crassumolides, sinularolides, durumolides and columnariols have shown capacity to block the expression of iNOS and/or COX-2 by LPS-activated RAW264.7 cells [ 34 ]. Some cembranoids have been identified as modulators of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathway [ 35 , 36 , 37 ]. Indeed, in recent years, anti-inflammatory activity for eunicellin-based diterpenoids isolated from soft corals, has been described [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thao and colleagues contributed a new polyhydroxylated steroid sarcopanol A (161) from the Vietnamese soft coral Sarcophyton pauciplicatum that inhibited tumor necrosis factor (TNF)-α and interferon (IFN)γ-induced expression of COX-2, iNOS, and intercellular adhesion molecule-1 (ICAM-1) in the spontaneously transformed immortal human keratinocyte cell line HaCaT via inhibition of NF-κB signaling pathway activation [181]. Thao and colleagues investigated the diterpenoid sinumaximol (162), isolated from the marine soft coral Sinularia maxima, and determined that it significantly inhibited TNF-α-induced NF-κB transcriptional activity in a human hepatocarcinoma HepG2 cell line, while concomitantly inhibiting the expression of pro-inflammatory iNOS and ICAM-1mRNA expression, thus supporting the "therapeutic potential as anti-inflammatory" of this compound [182]. Quang con colleagues determined that tanzawaic acid A (163), isolated from a marine fungus Penicillium sp.…”
Section: Anti-inflammatory Activitymentioning
confidence: 95%
“…[185][186][187]; two new briarane diterpenoids briaviolides E and I (170,171), isolated from the Taiwanese soft coral Briareum violacea [188]; a new pigmented phenazine compound dermacozine H (172), isolated from the actinomycete Dermacoccus abyssi sp. nov. strain MT1.1, isolated from a Mariana Trench sediment at a depth of 10,898 m [189]; a novel sesquiterpene dysifragilone A (173), isolated from the South China Sea sponge Dysidea fragilis [190]; a new xenicane 4α-hydroxypachylactone (174), isolated from a Chinese brown alga Dictyota plectens [191]; a polyketide comaparvin (175), isolated from the Taiwanese marine crinoid Comanthus bennetti [192]; two novel eunicellin-type diterpenoids hirsutalins N and S (176, 177) and a new tocopherol-derived metabolite hirsutocospiro A (178), isolated from the Taiwanese soft coral Cladiella hirsuta [193][194][195]; a new cembranoid isosinulaflexiolide K (179), isolated from cultured Taiwanese soft corals Sinularia sandensis and Sinularia flexibilis [196]; a novel 9,11-secogorgosteroid klyflaccisteroid F (180), isolated from the Taiwaneses soft coral Klyxum flaccidum [197]; new eunicellin-type diterpenoids krempfielins N (181), Q (182), and R (183), isolated from a Taiwanese soft coral Cladiella krempfi [198,199]; a methylfarnesylquinone (184), isolated from the Taiwanese marine brown alga Homeostrichus formosana [200]; a novel steroid monanchosterol B (185), isolated from the Korean sponge Monanchora sp. [201]; a oxygenated steroid derivative (186), isolated from the Vietnamese starfish Protoreaster nodosus [202]; a new spirobisnaphthalene rhytidenone C (187), isolated from an extract of a cultured fungal endophyte Rhytidhysteron sp.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%